Borane‐Mediated Vinylphosphane Cycloaddition to Conjugated Ynones. Issue 11 (17th December 2019) - Li, Jun; Daniliuc, Constantin G.; Kehr, Gerald; Erker, Gerhard
Abstract : Dimesitylvinylphosphane 4 reacts with a small series of conjugated ynones and B(C6 F5 )3 to give the five‐membered heterocyclic phosphorus containing products 8 . The reaction of allyldimesitylphosphane with dimethylacetylene dicarboxylate and B(C6 F5 )3 follows a related pathway to give the six‐membered phosphorus containing product 12 . Abstract : Dimesitylvinylphosphane undergoes a stepwise [3+2] type cycloaddition reaction with conjugated ynones to give the five‐membered phosphorus heterocyclic products.